The Gynecological Papyrus Kahun - Trindade Lopes, Helena; Gurgel Pereira, Ronaldo G. (IntechOpen, 2021)
The essential nature of Egyptian healing links religious notions and the so-called magical practices. It was wholly integrated with empiric-rational approaches to perform a multi-layered therapeutic. Ancient Egyptian medicine mirrors Egyptians' ethos and worldview. Thus, Egyptian medical papyri contribute to our better understanding of Egyptians cultural relation with diseases and cures. This book re-examines a short gynecological manual from the Papyrus University College 32057, housed at the Petrie Museum of Egyptian Archaeology, London. The volume presents thirty-four cases in hieroglyphics, transliteration, and translation. A comment section highlights cardinal data, classifies ingredients, and evokes the mental processes at work. The volume ends with a glossary of lexical elements.